Forensic science: A Beginner's Guide - Siegel, Jay 2009, 2016 (Grate Britain : Oneworld Publications, 2016)
What is forensic science and how is it used to solve a crime? How do you know if a red stain is blood or ketchup, or whose blood it is? Can computers really recognize your face in a crowd? How do scientists decide how old bones are, and trace who they once belonged to? Explore the fascinating, and sometimes gory, world of forensics, where science helps crack the case. Learn why it is important to secure a crime scene, why fingerprints are critical clues, and how DNA sampling works. Find out how maggots can reveal how long someone has been dead, or how a single fabric fiber can lead to the murderer. From the scene of the crime to testing in the laboratory, you will get to know how all the clues are put together to tell a story and reveal the guilty person. Discover how methods have changed since the days of Sherlock Holmes, the latest technology in use today, and techniques of the future.--
Previous edition: 2009.
In the wake of the phenomenal success of crime shows like CSI, forensic science has never been so popular. The obsessive attention that Grissom and his crew afford seemingly insignificant details, such as particles of dirt in a bullet wound and the presence of pollen in tyre tracks, have left audiences eager to know more about this field of study.
In this fully revised and updated edition, real-life examples come under the scalpel as forensic scientist Jay Siegel follows the course of evidence all the way from the crime scene to the court judgement. In Forensic Science: A Beginner s Guide, all major areas are covered, including drugs, trace evidence, pathology, entomology, odontology, anthropology, crime scene investigation and the law.
Includes index only.
Keywords: Forensic sciences; Criminal investigation; Criminals -- Identification; Evidence, Criminal; Forensic sciences; Criminal investigation; Criminals -- Identification; Evidence, Criminal; JUVENILE NONFICTION / Technology / How Things Work-Are Made; JUVENILE NONFICTION / Law & Crime; Criminal investigation; Criminals -- Identification; Evidence, Criminal; Forensic sciences; Juvenile nonfiction; Illustrated works; Instructional and educational works; Juvenile works; Trivia and miscellanea; Instructional and educational works; Illustrated works; Trivia and miscellanea